Impact of COVID-19 pandemic and lockdown on eye emergencies. Issue 6 (November 2021) - Poyser, Alicia; Deol, Sundeep S; Osman, Lina; Kuht, Helen J; Sivagnanasithiyar, Tharsica; Manrique, Roslyn; Okafor, Linda O; DeSilva, Ian; Sharpe, David; Savant, Vijay; Sarodia, Usman; Sarvananthan, Nagini; et al.
Background: To characterise and compare ocular pathologies presenting to an emergency eye department (EED) during the COVID-19 pandemic in 2020 against an equivalent period in 2019. Methods: Electronic patient records of 852 patients in 2020 and 1818 patients in 2019, attending the EED at a tertiary eye centre (University Hospitals of Leicester, UK) were analysed. Data was extracted over a 31-day period during: (study period 1 (SP1)) COVID-19 pandemic lockdown in UK (24th March 2020–23rd April 2020) and (study period 2 (SP2)) the equivalent 2019 period (24th March 2019–23rd April 2019). Results: A 53% reduction in EED attendance was noted during lockdown. The top three pathologies accounting for >30% of the caseload were trauma-related, keratitis and uveitis in SP1 in comparison to conjunctivitis, trauma-related and blepharitis in SP2. The overall number of retinal tears and retinal detachments (RD) were lower in SP1, the proportion of macula-off RD's (84.6%) was significantly ( p  = 0.0099) higher in SP1 (vs 42.9% in SP2). Conclusion: COVID-19 pandemic related lockdown has had a significant impact on the range of presenting conditions to the EED. Measures to stop spread of COVID-19 such as awareness of hand hygiene practices, social distancing measures and school closures could have an indirect role in reducing spread of infective conjunctivitis. The higher proportion of macula-off RD and lower number of retinal tears raises possibility of delayed presentation in these cases. Going forward, we anticipate additional pressures on EED and other subspecialty services due to complications and associated morbidity from delayed presentations.